2019
DOI: 10.3892/etm.2019.7580
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA ameliorates diabetic cardiomyopathy by inhibiting Grp78 and CHOP expression in STZ‑induced diabetes rats

Abstract: Diabetic cardiomyopathy (DCM), one of the common diabetic complications, causes a high rate of mortality in patients with diabetes. Tanshinone IIA (TSIIA), one of the components of Salvia miltiorrhiza (Danshen), has anti-oxidative stress activity and is widely used to treat diabetes-associated diseases. However, its efficacy on DCM remains unclear. The present study aimed to investigate the potential therapeutic function of TSIIA on DCM in an experimental diabetic rat model. Streptozotocin (STZ)-induced diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Increasing evidence suggesting that ER stress and associated apoptotic cell death are involved in the development of DCM [37][38][39][40]. In the present study, immunoblot analysis revealed significant increases in GRP78 (Fig.…”
Section: Dppi Deletion Prevents Diabetes-induced Endoplasmic Reticulum (Er) Stress As Well As the Associated Er Cell Death Pathwaysupporting
confidence: 68%
“…Increasing evidence suggesting that ER stress and associated apoptotic cell death are involved in the development of DCM [37][38][39][40]. In the present study, immunoblot analysis revealed significant increases in GRP78 (Fig.…”
Section: Dppi Deletion Prevents Diabetes-induced Endoplasmic Reticulum (Er) Stress As Well As the Associated Er Cell Death Pathwaysupporting
confidence: 68%
“…Therefore, in order to clarify the mechanism of GAS5 in DCM, STZ-induced diabetic rats and HG-processed H9C2 cells were established. Similar to the results obtained by Tao et al ( 35 ), STZ injection to rat myocardium resulted in decreased body weight and increased blood glucose concentration, indicating successful establishment of diabetic rats. Contrary to the increased expression levels of GAS5 in PBMCs from patients with type 2 diabetes, the present results revealed decreased expression levels of GAS5 both in the rat myocardium and HG-processed H9C2 cells, suggesting that GAS5 expression patterns differ according to the cell types in patients with DM.…”
Section: Discussionsupporting
confidence: 88%
“…The antihypertensive drugs, such as valsartan, are shown to downregulate CHOP expression and reduce cardiac remodeling in DCM (373,374). On the other hand, phytochemicals, such as matrine, have attracted attention in attenuating maladaptive ERSR (376) and preserving UPR ER signaling (61, 377), subsequently improving cardiac function in STZ-induced DCM. Moreover, vanadium derivative (55) and endogenous hormones, such as melatonin (379) and FGF21 (386,387), have been investigated for their cardioprotective role by suppressing oxidative stress-mediated ERSR and cell death in T2DM.…”
Section: Targeting the Upr Ermentioning
confidence: 99%